(untitled) (Research, Society and Development, 2023)
Due to the fact that alcohol consumption has increased, and that this molecule can promote several changes, the objective of this narrative review was to describe the metabolism of ethanol and its relationship with the intestinal microbiota, as well as the diseases associated with both. Articles were used in the elaboration of the narrative review. Alcohol dependence represents an important public health problem that affects millions of people worldwide. Chronic alcohol consumption is related to increased intestinal permeability, favoring significant changes in the composition of the intestinal microbiota and allowing bacterial components to be translocated and reach the portal, and systemic circulation. Bacterial products that travel through the circulation are recognized by cells of the immune system, which release pro-inflammatory cytokines and increase the formation of reactive oxygen and nitrogen species as well as cell stress. Alcohol consumption is also related to the qualitative imbalance of microorganisms in the large intestinal, where there is less abundance of Bacteroidetes and greater Proteobacteria in alcoholist individuals compared to healthy. It is concluded that chronic alcohol intake modifies the intestinal microbiota and contributes to intestinal dysbiosis.